Developing Learning Video Based on Plotagon in Civics Education Subject at Xaverius 3 Elementary School - Noviyani, Ni Ketut; Indriasari, B A. (International Journal of Business, Law, and Education, 2025)
This research aims to develop learning videos using the digital application Plotagon in the PPKN (Civics Education) subject for third-grade students at Xaverius 3 Elementary School in Palembang. The development is conducted using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The subject of the research consists of third-grade students, comprising three participants in the one-to-one stage, six participants in the small group stage, and fifteen participants in the field test. Data collection is conducted through interviews, tests, and questionnaires. The results show that the development of learning videos is deemed feasible, with percentages of 79.2% from material experts (valid category), 94.6% from language experts (very valid category), and 62.5% from video experts (sufficiently practical category). In the student trial stage, the video received a percentage of 86, 67% in the one-to-one test (a convenient category), and 77% in the small group test (a practical category), with an average of 81.83%, which falls into the practical category. Furthermore, the field test results show an average percentage of 80% in the convenience category. These results affirm that the Plotagon application-based learning video developed is suitable, practical, and effective for use in the learning process.